(untitled) (World Economics and Finance Bulletin, 2026)
This article examines current trends and expectations in the development of venture financing as a key instrument for supporting startup projects and small innovative enterprises. Using scientific literature, regulatory documents, official online resources, academic theories, and literature review, the study covers the institutional context of venture market growth in emerging economies. Special attention is given to the evolution of government policy in the field of venture financing and its impact on the creation of a national innovation ecosystem. The current state of the venture market and key priorities for its development are described